1997
DOI: 10.1038/sj.gt.3300353
|View full text |Cite
|
Sign up to set email alerts
|

Differential toxicity of ganciclovir for rat neurons and astrocytes in primary culture following adenovirus-mediated transfer of the HSVtk gene

Abstract: The toxicity of the suicide HSVtk gene approach is known to be targeted to DNA synthesis and, consequently, to dividing cells. This system is therefore useful for the treatment of brain tumors which contain dividing cells surrounded by a quiescent normal tissue. Adenoviruses are efficient vectors for the transfer of the HSVtk gene into the tumor but this can lead to the transduction of quiescent cells. In this study, we focused on the toxicity of the HSVtk/ganciclovir treatment for the two main cell types of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…This is precisely what makes such vectors interesting for tumor cell-targeted gene therapy. The most commonly used vec- 30,31 reported that adenoviral vectors can substantially transduce both cell types.…”
Section: Iu/ml Rcpv Contamination Of the Recombinant Virus Stocks Wamentioning
confidence: 99%
See 1 more Smart Citation
“…This is precisely what makes such vectors interesting for tumor cell-targeted gene therapy. The most commonly used vec- 30,31 reported that adenoviral vectors can substantially transduce both cell types.…”
Section: Iu/ml Rcpv Contamination Of the Recombinant Virus Stocks Wamentioning
confidence: 99%
“…Likewise, NRA were isolated from the brain of a rat embryo. 31 To evaluate the transduction efficiency of MVMpbased vectors at the cellular level, we next infected the different cell types at different multiplicities of infection (MOI) with a recombinant construct expressing the green fluorescent protein (GFP) gene. The proportion of cells expressing GFP was then quantitatively determined by flow cytometry 2 days after infection.…”
Section: Iu/ml Rcpv Contamination Of the Recombinant Virus Stocks Wamentioning
confidence: 99%
“…Instead, this vector has been used for the delivery of antitumor genes in the clinical setting. [35][36][37][38] Consideration of the prior immune Table 1). These results suggest that apoptosis may be a factor in the lack of ␤-galactosidase expression in U030.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similar results concerning toxicity to the liver and the brain have, meanwhile, also been reported by others. [7][8][9] Liver-related toxicity accompanying the treatment of colorectal metastases could be of increasing relevance because in the long run local treatment of this disease which allows at least some confinement of the vector to the target tissue will, due to the disseminated nature of the disease, be substituted by regional or systemic vector infusions, a method of application that has already been applied with some success for the treatment of colorectal liver metastases with an adenovirally transferred p53 gene. 10 One possible way to circumvent problems connected with tk gene expression in hepatocytes after adenoviral gene transfer is to use tissue-specific regulatory elements thereby restricting tk gene expression to the tumor cell.…”
Section: Correspondence: M Strauss Max-delbrü Ck-centrum Fü R Molekumentioning
confidence: 99%